The myths of Japanese quality - Eberts, Ray E. (Prentice Hall PTR, 1995)
"When it comes to Japan, many Americans have an inferiority complex. When we're told that our products, managers and schools are inferior to Japan's, we believe it instinctively. But it's not true." "In this important new book, Ray and Cindelyn Eberts dissect the myths of Japanese quality one at a time:" "Overall, American workers are 30% more productive than Japanese workers, yet over 40% of Japanese employees worry that job stress will kill them." "Japanese companies don't systematically use quality methods - Deming's or anyone else's - except when those methods fit their cultural preconceptions." "There's no evidence that Japanese students learn more in school, or that Japanese adults are more literate than Americans - and American high school graduates are 60% more likely to attend college." "By and large, Japanese companies are not more technologically advanced than American companies, and Japanese companies don't earn more patents than American companies." "Most Japanese companies aren't more responsive to their customers. Some are separated from their customers by as many as 30 layers of management." "The Japanese view of America is systematically distorted to emphasize the negative, even when the facts don't support it." "In short, the Japanese are human and imperfect, just like everyone else. There's no utopia across the Pacific. We'll have to find our own solutions, and we'll be better off if we start from realities. Not myths."--BOOK JACKET.